Simplified procedure to estimate the resistance parameters of transmission lines - Kurokawa, Sérgio [UNESP]; Asti, Gislaine Aparecida; Costa, Eduardo Coelho Marques; Pissolato, José (Springer Nature, 2013)
An alternative and simplified procedure is described to estimate the longitudinal resistances of transmission lines based on the real-time load profile. This method proposes to estimate the resistance parameters from the synchronized measurements of complex currents and complex voltages at the sending and receiving ends of transmission systems. The synchronized measurements can be in practice obtained using phasor measurement units (PMUs). © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Parameters estimation; Phasor measurement units.; Power systems; Transmission line theory; Load profiles; Phasor measurement unit (PMUs); Resistance parameters; Simplified procedure; Synchronized measurement; Transmission systems; Electric lines; Electric power system interconnection; Phasor measurement units; Standby power systems; Estimation